2020
DOI: 10.1634/theoncologist.2020-0808
|View full text |Cite
|
Sign up to set email alerts
|

Single-Agent Versus Double-Agent Chemotherapy in Concurrent Chemoradiotherapy for Esophageal Squamous Cell Carcinoma: Prospective, Randomized, Multicenter Phase II Clinical Trial

Abstract: The efficacy of single-agent chemotherapy was not significantly different from that of double-agent chemotherapy in concurrent chemoradiotherapy for inoperable esophageal squamous cell carcinoma. • Single-agent concurrent chemoradiotherapy had lower gastrointestinal and hematologic toxicity. • Overall survival and progression-free survival were not significantly different between single-and double-agent concurrent chemoradiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
1
5
1
Order By: Relevance
“…Efficacy in the dCCRT group was similar to that of the sCCRT group, although more grade 2–4 severe toxicities were observed in the dCCRT group, including myelosuppression, leucopenia, radioactive esophagitis, and gastrointestinal reaction. Differences in intensity of chemotherapy during RT did not affect the incidence of radiation pneumonia, which was essentially consistent with the results of Li et al 13 The results of Phase II clinical trial reported by Zhao et al 14 showed that the median disease-free survival times were 20 and 21 months for the single-agent and dual agent groups, respectively, with no significant differences. However, the incidence of myelosuppression and vomiting was significantly lower in the single-agent group.…”
Section: Discussionsupporting
confidence: 89%
“…Efficacy in the dCCRT group was similar to that of the sCCRT group, although more grade 2–4 severe toxicities were observed in the dCCRT group, including myelosuppression, leucopenia, radioactive esophagitis, and gastrointestinal reaction. Differences in intensity of chemotherapy during RT did not affect the incidence of radiation pneumonia, which was essentially consistent with the results of Li et al 13 The results of Phase II clinical trial reported by Zhao et al 14 showed that the median disease-free survival times were 20 and 21 months for the single-agent and dual agent groups, respectively, with no significant differences. However, the incidence of myelosuppression and vomiting was significantly lower in the single-agent group.…”
Section: Discussionsupporting
confidence: 89%
“…reported higher rates of efficacy and acceptable toxicity, with 36% of patients experiencing significant toxicity. 14 Much lower rates of severe esophagitis (5.8%) and hematologic toxicity (9.8%) were observed in the study by Zhao et al 36 compared to our study. In contrast, Takeuchi et al reported a high frequency of discontinued treatment (58%), mostly for hematologic toxicity.…”
Section: Discussioncontrasting
confidence: 58%
“…Secondly, neoadjuvant chemotherapy can lead to less extensive surgery and reduce the risk of local recurrences ( Dietz et al, 2018 ; van Ramshorst et al, 2018 ). Third, chemotherapy can enhance the local effect of radiotherapy during chemoradiation ( Geoffrois et al, 2018 ; Versteijne et al, 2020 ; Zhao et al, 2020 ). Finally, local response to palliative chemotherapy can decrease morbidity ( Vermorken et al, 2008 ; Judson et al, 2014 ; Loupakis et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%